2014
DOI: 10.3991/ijet.v9i9.4190
|View full text |Cite
|
Sign up to set email alerts
|

Educational Communication in Virtual Worlds and Videoconference

Abstract: Abstract-During the last few years an increase of the offered distance learning programs is observed, resulting in a need for corresponding tools. Within this context, the present study examines comparatively Virtual Worlds and Videoconferencing, as supporting tools for the educational communication and dialogue in distance learning. Analysing media theories, in order to compare the two media, we observe that the virtual space itself, and its relationship with the user, could affect the educational communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, since the participants knew that during the test they would not be allowed to use the notes that some of them took during the lecture, they did their best to memorise the lecture's content. In accordance with the MNT (Kock 2005), we suggest that the low level of medium naturalness in the oneway videoconferencing condition imposed a high cognitive load on the learners (Reychav, Warkentin and McHaney 2015;Tapsis and Tsolakidis 2015), which affected their scores on the achievement test. However, contrary to our first hypothesis and to the predictions of the MNT, participants in the one-way videoconferencing condition gained more inferential knowledge compared to those in the two-way videoconferencing condition.…”
Section: Discussionmentioning
confidence: 80%
“…However, since the participants knew that during the test they would not be allowed to use the notes that some of them took during the lecture, they did their best to memorise the lecture's content. In accordance with the MNT (Kock 2005), we suggest that the low level of medium naturalness in the oneway videoconferencing condition imposed a high cognitive load on the learners (Reychav, Warkentin and McHaney 2015;Tapsis and Tsolakidis 2015), which affected their scores on the achievement test. However, contrary to our first hypothesis and to the predictions of the MNT, participants in the one-way videoconferencing condition gained more inferential knowledge compared to those in the two-way videoconferencing condition.…”
Section: Discussionmentioning
confidence: 80%
“…According to Baber (2020), an effective interaction in online learning will lead to students' knowledge and better learning outcomes. As stated by Tapsis & Tsolakidis (2014), dialogue is an important dimension of any distance learning program. Ultimately, meaningful interaction is a necessary tool for enhancing the effectiveness of learning (MEHALL, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This research has also shown high participant satisfaction with the use of videoconferencing as an educational technology. Tapsis and Tsolakidis (2015) compare the advantages of using virtual worlds and videoconferencing as supporting tools for educational communication in distance learning. In their research they conclude that both platforms offer similar benefits, but the choice should be based on the specific requirements of the course subject.…”
Section: Introductionmentioning
confidence: 99%